Dermatoglyphic Patterns of the Medical Students and their Parents in Jammu Region of North India - Shalika Sharma; Koushal Kumar; Vanita Gupta (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background and Aims: Fingerprints have a general flow to the ridges that translates into three major pattern types;a whorl, loop, or arch. Pattern types are considered to be genetically inherited, but the individual details that makefingerprint unique are not. This descriptive study was conducted to differentiate the fingerprint patterns of MBBSstudents to their parents and to look for the uniqueness of fingerprint patterns in these medical graduates.Methods: To do this study, all ten fingerprints were examined from hundred first-year MBBS students of AcharyaShri Chander College Of Medical Sciences in the Jammu region of north India over 6 months from September 2019to February 2020 along with their two biological parents. Rolled fingerprints were obtained by carbon ink in all 300subjects divided into three groups(fathers, mothers, and students). Fingerprint patterns were examined by magnifyingglass under the supervision of a forensic expert of our institute and classified as loops, whorls, or arches.Results: The most frequent fingerprint pattern in all 3000 fingers examined is the loop pattern, which represents64.8%, followed by whorl pattern 30.8% and the least frequent pattern is arch(4.3%).these results were almost similarin medical graduates fingerprints patterns(loops 63.7%,whorls32.5% and arches 3.8%)indicating no difference fromother groups. Students show similar fingerprint patterns with those of their father’s fingers in 659 fingers, 468 asmatching loop patterns, 187 as a whorl, and 4 arch pattern types and the percent of similarity was 65.9% withhigher similarity in the RL 76% and LL72% fingers. Students show similar fingerprint patterns as that of theirmother in 685 fingers, 500 as matching loop patterns, 183 as a whorl, and 2 arch pattern types and the percent ofsimilarity was 68.5% with higher similarity in the RT78% and RL finger 78%. Fathers and mothers groups unrelatedgenetically when observed among themselves for similarity in fingerprint pattern showed similarity in 584 fingers,455 as matching loop patterns, 125 as a whorl, and 4 arch pattern types and the percent of similarity was 58.4% withhigher similarity in the LL77% and RL73% fingers.The statistical analysis for similarity correlation between students’ and fathers’ fingerprints shows a non-significantp-value found in the right index, left index, left middle, and left little fingers while other fingers show a significantp-value. Similarity correlation between students and mother shows a non-significant p-value found in the rightmiddle, left thumb, left index, left middle, and left little fingers while other fingers show a significant p-value.Similarity correlation between father and mother showed no significant correlation in all fingers except in the LLfinger, and negative correlation in RT, RM, and LM fingers.Conclusions: We concluded that the most common fingerprint pattern is the loop followed by whorl then archin MBBS graduates of our institute along with their parents. Moreover, the present study showed that fingerprintpatterns do not 100% match one of the parents; nevertheless, there is a similarity between offspring and their parents.